2020
DOI: 10.1093/jas/skaa380
|View full text |Cite
|
Sign up to set email alerts
|

Use of biochar by sheep: impacts on diet selection, digestibility, and performance

Abstract: The objective of this study was to determine the influence of biochar obtained from exothermic production of lodgepole pine (Pinus contorta) and quaking aspen (Populus tremuloides) on sheep performance and diet digestibility, and on preference for a ration enriched with this carbon-based material. Twenty-four lambs were housed in individual pens and assigned to one of three treatment groups (8 animals/group), where they received: 1) a 60:40 ration of alfalfa:barley (Control), 2) an isoenergetic and isonitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Terry et al [73] found no effect on body weight gain or DM intake in beef steers up to 2% biochar, but lean meat yield increased with the highest biochar level tested (2%). In lambs, 2% biochar kept feed intake and average daily gain unaffected, and improved DM intake [71], while up to 1.5% biochar was found to maintain DM intake and increase average daily gain and feed conversion ratio [72]. In addition, milk production of cows fed 0.5% (DM basis) activated carbon was improved [74].…”
Section: Effects Of Biochar In Vivomentioning
confidence: 96%
“…Terry et al [73] found no effect on body weight gain or DM intake in beef steers up to 2% biochar, but lean meat yield increased with the highest biochar level tested (2%). In lambs, 2% biochar kept feed intake and average daily gain unaffected, and improved DM intake [71], while up to 1.5% biochar was found to maintain DM intake and increase average daily gain and feed conversion ratio [72]. In addition, milk production of cows fed 0.5% (DM basis) activated carbon was improved [74].…”
Section: Effects Of Biochar In Vivomentioning
confidence: 96%
“…Silivong and Preston determined that supplementing goats diets with 1.1% biochar increased their weight by 8.9%, improved their feed conversion ratio from 15.5 to 11.4, and improved their digestibility (Silivong and Preston 2015 ). McAvoy et al ( 2020 ) investigated the effect of co-feeding quaking aspen and lodgepole pine biochar on the digestibility of the diet and overall sheep performance. They discovered that supplementing lambs' diets with biochar boosted digestibility and intake, as well as acetate generation.…”
Section: Animal Farmingmentioning
confidence: 99%
“…Charcoal and biochar from a variety of sources have been shown to increase feed conversion and increase body weight in broilers and strengthen eggshells, depending on the amount of material included in the feed supply [60][61][62]. Sheep demonstrated increased digestibility of feed that included biochar without an impact on weight gain [63]. Recently, it was shown that activated carbon could bind aflatoxin B 1 , deoxynivalenol, and zearalenone [5].…”
Section: Related Applications and Considerationsmentioning
confidence: 99%